2017
DOI: 10.1177/1474704917742384
|View full text |Cite
|
Sign up to set email alerts
|

Endorsement of Social and Personal Values Predicts the Desirability of Men and Women as Long-Term Partners

Abstract: A prospective romantic partner's desirability as a long-term partner may be affected by the values that he or she endorses. However, few studies have examined the effects of "values" on a person's desirability as a long-term partner. We hypothesized that individuals who endorse social values (vs. personal values) will be perceived as more desirable long-term partners (Hypothesis 1) and that the endorsement of social values will be especially desirable in a male (vs. female) long-term partner (Hypothesis 2). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
1
1
0
2
Order By: Relevance
“…This research examines a specific aspect of financial attitudes—money motives—which may affect relationship outcomes. In this, the research extends relationship research that has shown that attitudes held by one of the partners are associated with better relationship quality (e.g., self‐transcendence values; van der Wal et al, 2023; Ye et al, 2023; social values, Lopes et al, 2017; self‐control, Vohs et al, 2011). Previous research has also shown that similarity in values can benefit relationships (Gaunt, 2006; e.g., self‐direction values, Leikas et al, 2018; self‐transcendence values, Ye et al, 2023).…”
Section: Introductionsupporting
confidence: 66%
“…This research examines a specific aspect of financial attitudes—money motives—which may affect relationship outcomes. In this, the research extends relationship research that has shown that attitudes held by one of the partners are associated with better relationship quality (e.g., self‐transcendence values; van der Wal et al, 2023; Ye et al, 2023; social values, Lopes et al, 2017; self‐control, Vohs et al, 2011). Previous research has also shown that similarity in values can benefit relationships (Gaunt, 2006; e.g., self‐direction values, Leikas et al, 2018; self‐transcendence values, Ye et al, 2023).…”
Section: Introductionsupporting
confidence: 66%
“…Assim, evolutivamente, a expressão de tendências gananciosas por parte dos homens se traduz em maior ambição, energia aplicada em um dado objetivo e sucesso na trajetória (Buss & Schmitt, 1993). Na mesma direção, o maior endosso de valores pessoais dos homens pode gerar maior atração por parte as mulheres, uma vez que indica o potencial dos homens para aquisição de recursos (Lopes et al, 2017), aumentando a estima que as mulheres têm por eles (Gouveia et al, 2014). Em síntese, os homens valorizam mais a atratividade física do que as mulheres porque isto confere informações de valor reprodutivo, ao passo que as mulheres atribuiriam maior importância às capacidades de homens mais gananciosos para adquirir recursos, aumentando a probabilidade de que sua prole tenha condições favoráveis de sobrevivência (Buss, 2016).…”
Section: Discussionunclassified
“…tados, estima-se que o presente estudo tenha expandido as evidências empíricas sobre o traço de ganância no Brasil, nesta oportunidade, conhecendo seus correlatos valorativos e sociodemográficos, tendo em vista que mesmo frente à consensual TSP, tais elementos ainda são recentes em diferentes perspectivas neste campo (e.g., TFVH:Jonason et al, 2018; TMVH: Kajonius et al, 2015). Por fim, os achados foram discutidos sob o panorama da psicologia evolutiva, partindo da ideia de que a ganância pode representar uma pseudopatologia(Crawford & Anderson, 1989), isto é, um traço considerado socialmente indesejável, mas que pode implicar em benefícios psicossociais em certos contextos na sociedade (i.e., desenvolvimento econômico;Koehn et al, 2019), de forma específica de acordo com o sexo dos sujeitos.Assim, recomendam-se estudos futuros em diferentes estratos amostrais (e.g., adolescentes e adultos maduros) para fins de replicação dos achados encontrados, assegurando o controle de vieses de resposta, por exemplo, através de medidas implícitas (e.g., controle de efeito da desejabilidade social) e/ou controle por aquiescência (e.g., desenvolvimento de medidas com quantidade balanceada de itens positivos e negativos;Soto et al, 2008), assim como de estudos experimentais (e.g., se pessoas descritas como mais gananciosas são menos desejáveis como parceiros de relacionamentos a longo prazo;Lopes et al, 2017). Ademais, é fundamental contar com evidências adicionais de sua faceta aversiva mediante relações com a TSP, e com medidas de estratégias rápida de história de vida (i.e., Teoria da História de Vida; forma de alocação de recursos que os organismos utilizam para maximizar sua aptidão ao meio: maturação e reprodução precoces e baixa expectativa de vida;Roff, 1992).…”
unclassified
“…Schwartz [ 25 ] delineates values as “concepts or beliefs, pertaining to desirable end states or behaviors, transcendent of specific situations, guiding selection or evaluation of behaviors and events, and… ordered by relative importance”. Previous research has shown that, men and women differ in terms of their hierarchies of values [ 26 , 27 ] and the influence of their values on health-related behaviors, e.g., in the range of dietary choices [ 28 ], alcohol consumption and behaviors related to maintaining normal body mass [ 29 ]. According to the Public Opinion Research Centre (CBOS), [ 30 ] who conducted among a representative sample of Polish citizens, the values of “family happiness” and “health” are the most significant ones for the Polish population.…”
Section: Introductionmentioning
confidence: 99%